SILICON DIFFUSION IN SILICATE MINERALS - Bejina F.; Jaoul O. (My University, 1997)
Recently obtained silicon self-diffusion data, DSi = D0exp(- ΔH/RT), in silicates (quartz, vitreous silica, forsterite, San Carlos olivine and diopside) show a compensation law that is a linear relation, log D0 = log D* + ΔH/2.303 RT*. We find ΔH = 532.6 + 30.4 log D0 (ΔH in kJ/mol and D0 in cm2/s), which corresponds to log D* ~ -17.5 and T*, ~ 1588 K. D* represents a common value of DSi for all these silicates at T*, but also the value of DSi at ΔH = 0. It has, therefore, a pure entropic signification: D* = fa2vexp(ΔS/R); f is a geometrical factor, a the jump distance and v the Si-O vibrational stretching optic frequency almost common to all these silicates. Despite the wide range of enthalpies for Si diffusion in silicates, we propose that the compensation law outlines a unique mechanism for Si migration in minerals with structures based on the SiO4 tetrahedron.
Keywords: SILICON; DIFFUSION; SILICATES